Is surgery always indicated in rachitic coronal knee deformities? Our experience in 198 knees. (21st February 2017) - Prakash, Jatin; Mehtani, Anil; Sud, Alok; Reddy, Baccha K
Introduction: Defective mineralization of osteoid matrix prior to physeal closure causes rickets. Poor calcification of the cartilage matrix in the zone of provisional calcification causes flattened skull, rachitic rosary, bowed legs, coxa vara and brittle bones. The recent literature has seen an increase in the incidence of the disease in both developing and developed nations. We evaluated behaviour of lower limb deformities due to nutritional rickets in 117 patients. Materials and methods: A prospective study was conducted from January 2009 to December 2011 for clinical and radiological evaluation of knee deformities in nutritional rickets. A total of 117 patients with 198 coronal plane knee deformities between 2 years and 12 years age of rickets were enrolled in this study. Results: In our study, there were 65 genu varum and 133 genu valgum deformities. Seven genu varum (10.7%) and 37 genu valgum (28%) deformities were regarded as failure. Fifty eight genu varum got corrected completely obtaining an average of 5° of valgum in an average of 6.3 months. The average rate of spontaneous correction was 1.9° a month. Ninety six valgum got corrected obtaining an average of 4.7 valgum in an average of 13.3 months. The average rate of spontaneous correction was 0.92° a month. Conclusion: Most of the rachitic deformities get corrected with age. Genu varum is having better chances and a faster rate of correction as compared with genu valgum. Early surgery may be indicated in late presenting cases. We believe varum above 4 years and 18° of valgum above 9 years usually do not correct and may require surgical intervention.